Switched Beam Multi-Element Circular Array Antenna Schemes for 2D Single-Anchor Indoor Positioning Applications - Rattiya Kawdungta; Supakit Kawdungta; Danai Torrungrueng; Chuwong Phongcharoenpanich (IEEE Access, 2021)
This research investigates four switched-beam multi-element circular array antenna schemes operating at 2.4-2.5 GHz for two-dimensional (2D) single-anchor indoor positioning applications. The realization of the proposed antenna schemes involved two evolutionary stages: rectangular microstrip antenna with dielectric superstrate (i.e., element) and multi-element circular array antenna with radio frequency (RF) switch network. The number of elements of circular array antennas was varied between 4, 5, 6, and 8 elements. Multiple signal classification (MUSIC) algorithm was used to determine the direction of incoming signal and Friis transmission equation to estimate the transmission distance. Simulations were carried out, and results showed that the rectangular microstrip antenna with dielectric superstrate (one single element) achieved impedance matching ( $\vert S_{11}\vert < -10\,\,\text {dB}$ ) in the frequency range of 2.4-2.5 GHz, with unidirectional radiation pattern and 6.65 dBi antenna gain. In addition, four-, five-, six-, and eight-element circular array antenna prototypes were fabricated and experiments carried out in an indoor environment with two, three, and four incoming signals. The experimental results indicated that the eight-element circular array antenna could be deployed to reliably determine signal direction and distance, particularly for indoor localization with two incoming signals. The novelty of this work lies in the potential use of switched-beam multi-element circular array antenna schemes in place of conventional adaptive array antennas for 2D indoor localization. Compared with the conventional adaptive array antennas, the proposed multi-element circular array antenna schemes are relatively low-cost and easy to fabricate.
Keywords: Indoor and Outdoor Localization Technologies; Antenna Design and Analysis; Antenna Design and Optimization